Handbook of Digital Homecare Successes and Failures - Bos, Lodewijk; Dumay, Adrie; Goldschmidt, Leonard; Verhenneman, Griet; Yogesan, Kanagasingam (Springer eBooks., 2011)
This second volume of the Handbook of Digital Homecare reviews the attempts to develop new ICT services for digital homecare, i.e. services to deliver, maintain and improve care in the home environment using the latest ICT technology and devices. The book highlights the successful projects as well as failures of Digital homecare and provides several lessons learned to the wide audience of Health and ICT professionals.